How Many Securities Make A Diversified Portfolio in KLSE Stocks? - G . S. Gupta; Ch’ng Huck Khoon; Suhaimi Shahnon (Asian Academy of Management Journal, 2001)
The paper examines the relationship between the portfolio risk and the number of stocks in a portfolio for a given portfolio return across portfolio of the Malaysian stocks during the period September 1988 through June 1997 to determine the optimum size for a portfolio of stocks. A sample of 213 stocks traded on the Kuala Lumpur Stock Exchange (KLSE) are considered to form sets of portfolio using the Random Diversification Approach based on the Statman (1987) technique. The study has incorporated an additional statitistical test to supplement the Statman's to contain at least 27 randomly chosen securities. The study is extended to determine the diversified portfolio's size for each of the lending and borrowing investors based on the Statman (1987) methodology. A portfolio of 30 securities is found to give a well diversified portfolio for the borrowing investors and of 50 securities for the lending investors.